1986 Colloquium: Current Research in the Atlantic Provinces: Atlantic Geoscience Society

(untitled) (Atlantic Geoscience Society, 1986)
The 1986 Colloquium of the Atlantic Geosclence Society was held at the Wandlyn Inn, Amherst, Nova Scotia on January 17-18, 1986. The theme of the Colloquium was, "Current Research In the Atlantic Provinces." One of the highlights was the Avalon Workshop, which was held on the Friday. The workshop, organized by Sandra Barr, attracted nine papers, most of which will be published in subsequent Issues of Maritime Sediments and Atlantic Geology. At the regular sessions - on the Friday evening and all day Saturday - there were 24 oral presentations and 18 poster presentations. The quality of the papers was generally of a high standard and the subsequent discussions were Interesting and Informative. The biennial Rupert MacNell award for the best student paper was awarded to Dwanne Beattle of Dalhousle University for his paper, "Results of a gravity survey In Oarvell Bay Sabah (N. Borneo)." The meet Ing was enthusIastIca11y supported by about 125 part i cI pants, representing the federal and provincial governments, Industry and academia. The colloqulm was organized by Lalng Ferguson with the able support from Brenda Webb. Members of the Gesner Geology Society of Mount Allison University provided assistance on the Friday and Saturday, January 17-18. On behalf of the Atlantic Geosclence Society, we would like to thank Laing for running such a successful and enjoyable colloquium. In the following pages we publish the abstracts of papers presented at the meeting. The diversity of topics and the results Is an Indication of the vitality and depth of geological research In Atlantic Canada In the next decade.